AKSARA BALI DALAM PENULISAN PAPAN NAMA BERBAHASA ASING; SEKILAS TINJAUAN IMPLEMENTASI PERGUB BALI NO. 80 TAHUN 2018 - Made Reland Udayana Tangkas (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Pergub Bali Number 80 of 2018 concerning the Protection and Use of Balinese Language, Literacy and Literature and the Implementation of the Bali Language Month is to be like an oasis for lovers and observers of Balinese language, script and literature. With this regulation, the Balinese script in particular gained wider scope in the public sphere. Thus, Balinese script extends not only to Balinese but to international languages as Balinese itself is a world tourist destination. Government agencies, educational institutions, and the private sector have simultaneously followed the policy. A number of business entities have tried to put the Balinese script on the nameplate, but there are still many mistakes that occur. For this reason, it is necessary to have guidelines for writing foreign languages into the Balinese script. Some things that should be considered in writing a foreign language into Balinese are determining the pronunciation of the language as a starting point. Then the pronunciation is determined according to the sound system and the Balinese script spelling system is equipped with several corrections. Keywords: foreign language, Balinese script, pergub Bali